MEMAKNAI TEKS-TEKS DAKWAH DALAM FILM; PERSPEKTIF KOMUNIKASI PENYIARAN ISLAM - Primi Rohimi (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2013)
Abstract One of the KPI students competences was mastering communication theories related to mass media. So one of the competence application form was able to interpret the texts of proselytizing in the films by using KPI perspective. This paper gave application of proselytizing texts of several Indonesian Islamic-themed films. As we all knew, Indonesian Islamic films had been widely produced. The films that was interpreted in this paper were taken from the different missions and story criteria. So far, a film was only meant as a entertaining spectacle. By using the perspective of Islamic Broadcast Communications imbued with the spirit of Islamic proselytizing, a film could be interpreted as a media of proselytizing. Proselytizing messages could be interpreted from the texts in film, i.e. scenes, dialogue, background, and others. Messages that can be interpreted from it are religious, social, moral and humanitarian values. Keywords: meaning, proselytizing text, film, islamic broadcast communications Salah satu kompetensi mahasiswa Program Studi KPI adalah menguasai teori-teori komunikasi terkait dengan media masa. Maka wujud dari aplikasi kompetensi ini salah satunya adalah bisa memaknai teks-teks dakwah dalam film dengan perspektif KPI. Tulisan ini memberikan aplikasi pemaknaan teks-teks dakwah dari beberapa film Indonesia bertema Islam. Seperti sudah jamak diketahui, film-film Indonesia bertema Islam sudah banyak diproduksi. Film-film yang dimaknai dalam tulisan ini diambil dengan kriteria perbedaan misi dan cerita. Selama ini film hanya dimaknai sebagai tontonan yang berfungsi menghibur. Dengan perspektif Komunikasi Penyiaran Islam yang dijiwai spirit dakwah, film bisa dimaknai sebagai media dakwah. Pesan-pesan dakwah bisa dimaknai dari teks-teks dalam film baik adegan, dialog, latar, dan lainnya. Pesan-pesan yang dapat dimaknai dari film di antaranya nilai-nilai religius, sosial, moral dan nilai-nilai kemanusiaan lainnya. Kata Kunci: memaknai, teks-dakwah, film, komunikasi penyiaran Islam